PARADIGMA HUKUM DAN ETIKA ISLAM DALAM TRANSAKSI E-COMMERCE: PARADIGMA HUKUM DAN ETIKA ISLAM DALAM TRANSAKSI E-COMMERCE - RUSLAN JAYADI (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2024)
The purpose of this article is to try to answer current technological developments that are occurring today. The internet, which was initially used by several groups as a medium for transforming scientific and academic data, has now been used in almost all aspects of people's lives, including online buying and selling transactions or E-commerce. E-Commerce transactions carried out by sellers and buyers via the internet. This research aims to analyze and understand the Islamic legal and ethical paradigm in e-commerce transactions. This research method uses library research, namely research carried out by collecting data and theoretical foundations by studying books, scientific works, results of previous research, related journals, related articles and sources related to research in accordance with The research researched was then analyzed qualitatively and then presented descriptively. The results of this research can be concluded that online buying and selling transactions in E-commerce in their application have attempted to adapt Islamic business ethics, which is one of the forms of greeting transaction contracts in Islamic jurisprudence. And then we can answer people's concerns about e-commerce or online buying and selling regarding legal clarity.